A cytosolic pentatricopeptide repeat protein is essential for tapetal plastid development by regulating OsGLK1 transcript levels in rice. Issue 5 (5th April 2022) - Zheng, Shaoyan; Dong, Jingfang; Lu, Jingqin; Li, Jing; Jiang, Dagang; Yu, Haopeng; Ye, Simiao; Bu, Wenli; Liu, Zhenlan; Zhou, Hai; Ding, Yiliang; Zhuang, Chuxiong
Summary: Most plant pentatricopeptide repeat (PPR) proteins localize to and function inside plastids and mitochondria. However, the function of PPRs that only localize to the cytoplasm remains unknown. Here, we demonstrated that the rice ( Oryza sativa ) PPR protein CYTOPLASM‐LOCALIZED PPR1 (OsCPPR1) contributes to pollen development and localizes to the cytoplasm. Knocking down OsCPPR1 led to abnormal plastid development in tapetal cells, prolonged tapetal programmed cell death (PCD) and tapetum degradation, and significantly reduced pollen fertility. Transcriptome analysis revealed that the transcript level of OsGOLDEN‐LIKE1 ( OsGLK1 ), which encodes a transcription factor that regulates plastid development and maintenance, was significantly higher in the OsCPPR1 knockdown plants compared to wild‐type plants. We further determined that OsCPPR1 downregulates OsGLK1 transcription by directly binding to the single‐stranded regions of OsGLK1 mRNAs. Overexpression of OsGLK1 resulted in abnormal tapetum and plastid development, similar to that seen in OsCPPR1 knockdown plants, and suppression of OsGLK1 partially restored pollen fertility in the OsCPPR1 knockdown plants. We therefore conclude that OsCPPR1 suppresses OsGLK1 in the regulation of plastid development and PCD in the tapetum. Our work revealed novel functions for a cytosolic PPR, demonstrating the diverse roles of PPRs in plants and identifying a new regulatory mechanism for regulating pollen development in rice.